Socioeconomic Variation in Motivations for Ritual Practice - Dimitris Xygalatas; Peter Maňo (Religions)
This paper investigates socioeconomic variation in motivations for ritual practices among Mauritian Hindus. Using cultural domain analysis, we explore individuals’ reported reasons for engaging in a variety of religious rituals. Our findings demonstrate significant intra-cultural diversity driven by social stratification. Specifically, we observe that those of lower social standing appear primarily motivated by existential concerns related to material security and safety, while higher-status individuals view these practices as platforms for personal and social enrichment, as they are more preoccupied with self-actualization, spiritual connection, and social affirmation, reflecting a more abstract engagement with religious practices. Our findings reveal the adaptability of ritual practices to meet a wide range of human needs across varying life circumstances, as rituals can be differentially negotiated by individuals within the same cultural context depending on the specific socioecological niches they occupy. Moreover, they highlight the role of culture as a dynamic and distributed system with important implications for anthropological theory and practice.